Seroprevalence of Immunoglobulin G (IgG) and Immunoglobulin M (IgM) and Risk Factors of Toxoplasmosis for A sample of Pregnant Women in Baghdad - Abdul Mohammed Al-Rawazq, Huda Sahib (AL-Kindy College Medical Journal, 2019)
Background: Toxoplasmosis is a very common infection caused by the obligate intracellular protozoan parasite. This parasite is called Toxoplasma gondii widely distributed around the world . Toxoplasma gondii can be vertically transmitted to the fetus during pregnancy and may cause wide range of clinical manifestations in the offspring. Objective: To determine seroprevalence Immunoglobulin G (IgG) and Immunoglobulin M (IgM ) to toxoplasma gondii among pregnant women and to identify the risk factors. Type of the study: A cross-sectional study. Methods: A total of 110 blood samples of pregnant women were collected from private laboratory for Dr. luay Ibrahim to Pathogenesis Analyses in Baghdad Al-Mansour- 14 Ramadan street . Which obtained during the period from 1st March 2016 till the 30th June 2016. Data was collected by using direct interviewing questionnaire sheet concerning their ages of pregnant women between (less than 20 to more than 40 years old), place of residence ( urban, rural), level of education (illiteracy, literacy), number of pervious abortion (one, two, three or more), contact with ( cat and other domestic animal or no animal in house). The diagnosis is based on IgG and IgM antibodies of Toxoplasma gondii were measured using a commercial Kit ( Cobas Toxo IgG, Toxo IgM) according to the Roche Diagnostic manufacturer’s instructions. Each blood was analyzed for the presence of Toxoplasma gondii by identifying serum IgG and IgM antibodies using Enzyme-linked Immunosorbent Assay (ELISA). Results: A total of 110 pregnant women were enrolled and screened for the presence of anti- toxoplasma IgG and IgM antibodies. The seroprevalence of Toxoplasma gondii IgG and IgM antibodies result revealed that 40 (63.4 %) of 110 pregnant women were positive for anti-toxoplasma-antibody IgG and 70 (63.6 %) of 110 were negative for anti-toxoplasma-antibody-IgG while revealed that 16 (13.6 %) of 110 pregnant women were positive for anti-toxoplasma-antibody IgM and 94 (86.4 %) of 110 were negative for anti-toxoplasma-antibody IgM. Conclusions: the present study shows that anti-Toxoplasma IgG Ab are higher than anti-Toxoplasma IgM Ab in pregnant women between the age group 20 to 30 years in literacy educational level and rural area also recorded the highest rates of seropositivity among women with only one previously abortion in contact with cats are more affected.